FRACTIONAL REVERSE BANKING DAN FIAT MONEY: PROBLEMATIKA SISTEM MONETER KONVENSIONAL DALAM PERSPEKTIF SYARIAH - Afiyah Zahrah; Juwita Sifas Sembiring; Ahmad Faturrahman (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This study critically examines the Fractional Reserve Banking (FRB) and fiat money systems within the framework of the conventional monetary system and their relevance to Islamic financial principles. The main questions raised are how the practice of money creation through FRB and the use of fiat money impacts economic stability and social justice, and how Islamic economics offers a more equitable alternative. The analysis shows that FRB and fiat money contribute to imbalances in the monetary and real sectors, as well as giving rise to the risk of inflation and a crisis of confidence. In contrast, an Islamic monetary system based on real assets and the principle of profit-sharing offers a more stable and equitable solution, free from elements of usury, gharar, and speculation. These findings reinforce the urgency of reforming the global monetary system toward a model that aligns with Islamic values ??of justice and balance.